A Case Series On Fatal Self-Inflicted Cut Throat Injuries Reported At An Autopsy Centre Of An Apex Hospital Of West-Bengal, India (Journal of Forensic Medicine & Toxicology, 2026)
Of the various methods adopted for committing suicide, suicide by inflicting cut throat injuries are painful, hence rare. Fatal cut throat injuries are mostly homicidal. In cases of fatal cut throat injuries, findings noted over neck and body does not conclusively determine the manner of death. Features classically present in suicidal cut-throat injuries may be present in homicides and vice-versa. Thus, they may be misleading or confusing. In such cases the findings of the Postmortem examination alone are insufficient to opine whether the death is suicidal or homicidal. Hence, along with the postmortem report of the victim, reports of police inquest, on the circumstances, mental state and relevant history of the victim are important considerations. Corroborating the wound with the recovered weapon, report of the Forensic Science Laboratory on the place of occurrence and on the materials preserved during Autopsy should be incorporated to form a conclusive opinion on the cause and manner of death in cases of fatal cut-throat injuries. A series of three such rare cases, has been illustrated. Diverse aspects of medicolegal investigation that ultimately led to forming a conclusive opinion on the manner of death has been described. This series of cut-throat injuries demonstrates the importance of inclusion of all aspects of forensic investigation to conclude on the suicidal manner of death.
Keywords: fatal; self-inflicted; cut-throat injuries